THE COMPREHENSIVE COMPARISON OF THE EFFICACY OF FIRST-LINE DRUGS IN THE TREATMENT OF TYPE II DIABETES: METFORMIN, GLP-1 AGONISTS, AND SGLT2 INHIBITORS - Anna Kamieniak; Dominika Gieroba (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Type II diabetes is a chronic metabolic disease characterized by hyperglycemia. The goal of diabetes treatment is to achieve normal blood glucose levels and prevent complications arising from diabetes. Currently, there are many groups of antidiabetic drugs available, differing in their main indications for use, mechanism of action, and side effects, which allow the selection of the most effective and best tolerated treatment method for a specific patient. Objective: The objective of this review was to compare the efficacy of drugs used as first-line treatments for type II diabetes, namely metformin, glucagon-like peptide-1 (GLP-1) receptor agonists, and sodium-glucose cotransporter 2 (SGLT2) inhibitors, also known as flozins, taking into account their limitations and adverse effects. Method: In order to compare the effectiveness of metformin, GLP-1 agonists, and SGLT2 inhibitors in the treatment of type II diabetes, a systematic review was conducted between 2020 and 2025, covering the PubMed database. Key words such as type II diabetes, metformin, GLP-1 receptor agonist, MALA, SGLT2 inhibitors were used. Conclusions: The comparison shows that metformin, GLP-1 agonists, and SGLT2 inhibitors are effective drugs used in the treatment of type II diabetes, and the choice of the appropriate drug depends on the patient’s condition, comorbidities, and the desired effects. SGLT2 inhibitors are the best choice for patients with heart failure and renal failure, while GLP-1 agonists are the most suitable for patients with high cardiovascular risk, as they reduce the risk of heart attack or stroke. Metformin, by increasing the sensitivity of peripheral tissues to insulin, is used in the treatment of both diabetes and insulin resistance. In addition, it is the cheapest of the compared groups of drugs, which may be an important aspect in the selection of therapy for individual patients coming from poor environments. All three groups lower blood glucose without the risk of hypoglycemia. Side effects mainly include gastrointestinal disorders (metformin, GLP-1) and urinary tract infections (SGLT2). Summing up the above conclusions, it can be stated that the choice of drug in diabetes therapy should mainly depend on the patient’s comorbidities.